Easter Egg Symbolism in Lithuania Minor - Blockytė-Naujokė, Kristina (Acta humanitarica academiae Saulensis, 2025)
The biggest Lietuvininkai holiday connected with the ceremonial act of egg painting was Easter. In general, rites of a communal nature dominated in the calendar holidays of Lithuania Minor: attending church in the morning of the holiday, whipping with juniper or birch branches on the first day of Easter (in some locations – on the second), giving of painted Easter eggs and so on. It should be noted that from the very first descriptions of the Easter celebration in Lithuania Minor and to the present day, the main holiday symbol has been an egg and ceremonial acts related to it. Thus, the Easter egg and its related ritual actions in the Easter traditions and rites in Lithuania Minor constitute the object of the article. The archaic model of the Easter celebration in Lithuania Minor is characterized by the elements related to the symbolism of the egg, which include the ritual function and archaic semantics of egg painting, the custom of Easter egg gifting and well-wishing, and various games with eggs (breaking, rolling). Rituals with this main holiday attribute – the egg – played an exceptional role, so custom and tradition in Lithuania Minor changed very slowly. In the late 19th – early 20th centuries, in Lithuania Minor, the ritual tradition noticeably loses its existential significance; rituals become customs, and ritual functions are replaced by traditions that form regional ethnic identity. The magical meaning of egg gifting is gone, the tradition of Easter greetings is gaining popularity, and a new element is emerging – hiding eggs in the nests made in the garden and telling children that they are brought by the Easter bunny. The modern model of Lithuania Minor holidays tries to combine ethnic traditions with the needs of the consumer-oriented modern society. Easter in Lithuania is unimaginable without Easter eggs. Of course, the techniques of egg decoration have slightly changed, but the activities remain identical – Easter eggs are given as presents and various games are played with them – rolling and trying to crush the opponent’s eggs. Thus, based on the written sources recorded in the territory of Lithuania Minor and on modern ethnographic narratives, it becomes obvious that the interpretations of Easter celebration provided by the informants are related to the social and cultural environment in which they live. Therefore, the data about Easter in Lithuania Minor obtained from surviving descriptions and living witnesses are interesting and studied as a monument of history and ethnography, a testimony to the evolution of spiritual values of the area’s population.